Impacts of COVID-19 on Air Quality through Traffic Reduction - Hwang, Hyemin; Lee, Jae Young (International Journal of Environmental Research and Public Health, 2022)
In 2020, the first case of COVID-19 was confirmed in Korea, and social distancing was implemented to prevent its spread. This reduced the movement of people, and changes in air quality were expected owing to reduced emissions. In the present paper, the impact of traffic volume change caused by COVID-19 on air quality in Seoul, Korea, is examined. Two regression analyses were performed using the generalized additive model (GAM), assuming a Gaussian distribution; the relationships between (1) the number of confirmed COVID-19 cases in 2020–2021 and the rate of change in the traffic volume in Seoul, and (2) the traffic volume and the rate of change in the air quality in Seoul from 2016 to 2019 were analyzed. The regression results show that traffic decreased by 0.00431% per COVID-19 case; when traffic fell by 1%, the PM10, PM2.5, CO, NO2, O3, and SO2 concentrations fell by 0.48%, 0.94%, 0.39%, 0.74%, 0.16%, and −0.01%, respectively. This mechanism accounts for air quality improvements in PM10, PM2.5, CO, NO2, and O3 in Seoul during 2020–2021. From these results, the majority of the reduction in pollutant concentrations in 2020–2021 appears to be the result of a long-term declining trend rather than COVID-19.
Keywords: Air Pollutants; Air Pollution; COVID-19; Environmental Monitoring; Humans; Particulate Matter; SARS-CoV-2; Air quality; COVID-19; Generalized additive model; Seoul; Social distancing; Traffic